IMPROVING CHILDREN’S VOCABULARY LITERACY THROUGH THE COMMUNICATIVE METHOD IN LANGUAGE LEARNING - Dilnoza Oblokulova, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
This article examines the effectiveness of the communicative method in improving children’s vocabulary literacy in language learning. Traditional vocabulary instruction often emphasizes memorization, limiting learners’ active word use. The study aims to analyze how communicative language teaching supports meaningful vocabulary development among young learners. Based on a qualitative review of relevant theoretical and empirical studies, the findings show that communicative activities enhance vocabulary retention, learner engagement, and functional language use. The article concludes that the communicative method offers an effective, learner-centered approach to developing children’s vocabulary literacy.